What Happened To You? : Conversations on Trauma, Resilience, and Healing - Perry, Bruce D. (Bruce Duncan), 1955-; Winfrey, Oprah (New York : Flatiron Books, 2021)
Oprah Winfrey, sharing stories from her own past, and a renowned brain development and trauma expert discuss the impact of trauma and adversity and how healing must begin with a shift to asking, "What happened to you?" rather than "What's wrong with you?"
Making sense of the world -- Seeking balance -- How we were loved -- The spectrum of trauma -- Connecting the dots -- From coping to healing -- Post-traumatic wisdom -- Our brains, our biases, our systems -- Relational hunger in the modern world -- What we need to know.
"An Oprah book" -- From title page
Includes bibliographical references (pages 299-301)
Keywords: Psychic trauma; Life change events -- Psychological aspects; Resilience (Personality trait); Mental healing